High-corrosion-resistant and wear-resistant tungsten-based hard alloy and preparation method thereof

By high-temperature sintering of tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofibers with graphene-coated core-shell composite powder, the problem of easy corrosion and wear of tungsten carbide-cobalt cemented carbide was solved, and the material's high corrosion and wear resistance was improved.

CN121109910AActive Publication Date: 2025-12-12河北恒洋材料科技有限公司

Patent Information

Application Number
CN202511360678.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-12
Estimated Expiration
2045-09-23

AI Technical Summary

Technical Problem

Tungsten carbide-cobalt cemented carbide is susceptible to corrosion and wear, which leads to a decline in material performance and a shortened lifespan.

Method used

A multi-scale lubrication system was constructed by high-temperature sintering of tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofibers with graphene-coated core-shell composite powder. Through physical anchoring and chemical bonding, the interfacial bonding was enhanced, reducing defects and improving bending strength, corrosion resistance and wear resistance.

Benefits of technology

It significantly improves the bending strength, corrosion resistance, and wear resistance of tungsten-based cemented carbide, optimizes the material's performance, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a high-corrosion-resistant and wear-resistant tungsten-based hard alloy and a preparation method thereof, and relates to the technical field of hard alloys. The high-corrosion-resistant and wear-resistant tungsten-based hard alloy is composed of tungsten-based composite oxide and molybdenum disulfide boron nitride hybrid nanofibers and graphene coated core-shell composite powder. Tungsten-based composite oxide and molybdenum disulfide boron nitride hybrid nanofibers and graphene-coated core-shell composite powder are subjected to high-temperature sintering, the interface bonding performance of the nanofibers and the graphene-coated core-shell composite powder is enhanced in a physical anchoring and chemical bonding mode, defects are reduced, external stress is effectively transmitted, the barrier protection effect can be enhanced, permeation of a corrosion medium is fully isolated, and the corrosion resistance of the corrosion medium is improved. And a multi-scale lubricating system is also constructed, and the abrasion of substances such as tungsten carbide and cobalt is reduced, so that the bending strength, the corrosion resistance and the abrasion resistance are remarkably enhanced, the use performance of the tungsten-based hard alloy is optimized, and the service life of the tungsten-based hard alloy is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of hard alloy, and particularly relates to a high-corrosion-resistance and wear-resistance tungsten-based hard alloy and a preparation method thereof. BACKGROUND

[0002] The hard alloy is a composite material sintered by high-hardness metal carbide (such as tungsten carbide and titanium carbide) and metal binder phase (such as cobalt and nickel) through a powder metallurgy process, wherein the tungsten carbide-cobalt hard alloy is the most typical and most widely used hard alloy system, the tungsten carbide-cobalt hard alloy has high hardness, high heat resistance, high toughness, high strength and good wear resistance, and is widely used in the production of cutting tools, precision molds and wear-resistant parts, and becomes an irreplaceable material in the fields of cutting tools, mining equipment and military equipment.

[0003] The existing technology mainly has the following problems: The tungsten carbide-cobalt hard alloy, especially the cobalt binder phase, is easily affected by corrosion and wear, which leads to the decline of the use performance and the shortening of the service life of the material. SUMMARY

[0004] In view of the above problems, the present application provides a high-corrosion-resistance and wear-resistance tungsten-based hard alloy, which comprises the following components in parts by weight: 20-30 parts of tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber and 80-90 parts of graphene-coated core-shell composite powder.

[0005] The tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber is made of the following components in parts by weight: 4-6 parts of copper-nickel bimetallic MOF nanoparticles, 10-20 parts of ammonium metatungstate, 8-10 parts of polyvinylpyrrolidone, 3-5 parts of sodium molybdate dihydrate, 6-8 parts of thiourea, 0.8-1 part of boron nitride and 4-5 parts of Dow Corning Z-6020 silane coupling agent.

[0006] The graphene-coated core-shell composite powder is a core-shell structure powder obtained by first subjecting tungsten carbide powder, cobalt powder and nanometer ceria powder to ball milling and plasma activation treatment and then growing a graphene coating layer on the surface in situ.

[0007] The preparation method of the tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber specifically comprises the following steps: (1) 1.0-1.2 g of copper nitrate trihydrate and 0.4-0.6 g of nickel nitrate hexahydrate are dissolved in 15 mL of deionized water, stirred for 0.5-1 h to form solution I for standby, 0.8-1.0 g of trimesic acid is dissolved in 25 mL of anhydrous ethanol, stirred for 0.5-1 h to form solution II for standby, then solution I and solution II are mixed, 0.2-0.4 g of polyvinylpyrrolidone is added, stirred uniformly, and placed in a reaction kettle at 110-120°C for 10-12 h of hydrothermal reaction, the product is washed with anhydrous ethanol for 3-5 times, dried at 60°C under vacuum, the copper ions, nickel ions and trimesic acid are combined by coordination bond to form a bimetallic three-dimensional porous framework structure, the porous structure and high specific surface area help the uniform dispersion of tungsten species in the subsequent process, avoiding particle agglomeration in the calcination process, and copper-nickel bimetallic MOF nanoparticles are obtained; (2) The copper-nickel bimetallic MOF nanoparticles in step (1) are dispersed in 6 mL of N,N-dimethylformamide solvent, ultrasonic for 30-50 min, then ammonium metatungstate and polyvinylpyrrolidone are added, stirred for 20-30 min to obtain a precursor spinning solution, an electrospinning technology is used, a voltage of 10-18 kV is set, a pushing rate of 0.03-0.05 mm / s is set, the collected fiber is placed in a crucible, dried at 50-60°C for 1-2 h, then calcined in air at a heating rate of 1°C / min at 500-550°C for 1-2 h, the precursor spinning solution is stretched into a fiber under a high-voltage electric field, and a continuous and uniform porous nanofiber grid structure is formed after calcination, wherein copper oxide, nickel oxide and part of tungsten trioxide generated by pyrolysis of copper-nickel bimetallic MOF nanoparticles react to form CuWO4 / NiWO4 composite oxide, which has high hardness and chemical inertness, enhances wear resistance and corrosion resistance, and at the same time, CuWO4 / NiWO4 composite oxide and unreacted tungsten trioxide together form the rigid structure of the fiber, which effectively resists deformation and loss during the wear and corrosion process, and tungsten-based composite oxide nanofiber is obtained; (3) Dissolve sodium molybdate dihydrate and thiourea in 30 mL of deionized water, then add the tungsten-based composite oxide nanofiber described in step (2), ultrasonic dispersion for 10-20 min, adjust the pH to 4.0, then react at 180-200°C for 10-12 h, the product is washed with 80% ethanol solution for 3-5 times, vacuum dried at 60°C, then annealed at 350-400°C for 1-2 h in 2% hydrogen and 98% argon atmosphere, a molybdenum disulfide coating layer is formed on the surface of the tungsten-based composite oxide nanofiber by hydrothermal sulfidation reaction, giving the surface toughness characteristics, forming a rigid and flexible fiber structure, the Mo-O-W covalent bond is formed between the molybdenum disulfide and the oxygen vacancies on the surface of the tungsten-based composite oxide nanofiber, enhancing the interfacial bonding strength, reducing stress concentration, the layered structure of molybdenum disulfide can slip when stressed, absorbing part of the mechanical energy, avoiding brittle fracture of the fiber, enhancing the bending strength, the low interlayer shear strength of molybdenum disulfide can reduce the friction coefficient, reduce surface wear, at the same time, a protective film is formed on the material surface during friction, avoiding direct contact with the fiber core, and the molybdenum disulfide can form a passivation layer in a humid environment, blocking the penetration of corrosive media, obtaining tungsten-based composite oxide@molybdenum disulfide nanofiber; (4) Disperse 0.08-0.1 g of boron nitride in 20 mL of 90% ethanol solution, add 0.4-0.5 mL of Dow Corning Z-6020 silane coupling agent, ultrasonic treatment for 40-50 min, obtaining boron nitride suspension for use, then immerse the tungsten-based composite oxide@molybdenum disulfide nanofiber described in step (3) in the boron nitride suspension, stir at 50-60°C for 1-2 h, vacuum dried at 80°C, and finally annealed at 300-320°C for 0.5-1 h, the boron nitride is anchored on the surface of the molybdenum disulfide by the Dow Corning Z-6020 silane coupling agent, forming a coating and modification layer on the tungsten-based composite oxide nanofiber, the double amino functional groups form Si-O-W / Mo covalent bond and hydrogen bond with the oxygen vacancies and sulfur vacancies on the surface of the fiber, significantly enhancing the interfacial bonding strength, filling the surface defects of the fiber, reducing stress concentration and improving the bending strength, the lubricity of molybdenum disulfide and the hard property of boron nitride synergistically protect the fiber core from being worn, furthermore, the dense barrier formed by molybdenum disulfide and boron nitride effectively reduces the penetration of corrosive media, among which the hydrophobicity and chemical inertness of boron nitride can block the contact between the corrosive medium and the fiber matrix, obtaining tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber; Preferably, in step (2), the adding amount of ammonium metatungstate is 1.0-2.0 g, and the adding amount of polyvinylpyrrolidone is 0.8-1.0 g; the ammonium metatungstate is calcined and decomposed to generate tungsten trioxide as a main phase material, which provides a rigid skeleton for the fiber to resist deformation under external force; the polyvinylpyrrolidone acts as a high polymer template to form a uniform precursor with the ammonium metatungstate and copper-nickel bimetallic MOF nanoparticles, thereby ensuring continuous and uniform fibers during electrospinning; the polyvinylpyrrolidone is thermally decomposed to form pores, thereby improving the toughness of the fiber and relieving stress concentration, so as to enhance the bending strength; Preferably, in step (3), the adding amount of sodium molybdate dihydrate and thiourea is 0.3-0.5 g and 0.6-0.8 g, respectively; the sodium molybdate dihydrate and the thiourea provide a molybdenum source and a sulfur source, respectively, so as to form a molybdenum disulfide coating layer; sufficient thiourea can reduce sulfur vacancies in the molybdenum disulfide, avoid defects from becoming corrosion initiation points, and enhance the interface bonding between the molybdenum disulfide and the fiber, thereby improving the wear resistance; Preferably, in step (4), the grade of the Dow Corning Z-6020 silane coupling agent is OFS-6020; the Dow Corning Z-6020 silane coupling agent contains a diamino functional group, which can form stronger hydrogen bonds and covalent bonds with the molybdenum disulfide and boron nitride, thereby reducing interface defects and reducing the risk of wear and tear.

[0008] The application further provides a preparation method of the high-corrosion-resistant and wear-resistant tungsten-based hard alloy. S1, the tungsten carbide powder, cobalt powder, nano cerium dioxide powder according to the mass ratio 10:3:1-2 is loaded into the ball mill jar in turn, the ball to powder ratio is 5:1, then 0.8-1.0% of the total mass of the powder is added stearic acid, first ball milling at 180-200 rpm for 8-10 h, then the speed is adjusted to 280-310 rpm interval ball milling for 1-2 h, during the interval ball milling, ball milling for 30 min, pause for 10 min, then dry mixing at 300 rpm for 3-4 h, and high-purity argon is used as the protective atmosphere, the mixed powder obtained is treated by hydrogen plasma, the power is 80-120 W, the time is 10-30 min, finally the mixed powder after plasma treatment is put into a porcelain boat and pushed into a tube furnace, sealed, vacuumed and filled with nitrogen, repeated three times to complete gas replacement, the temperature is raised to 750-800 DEG C at a rate of 5 DEG C / min, and a mixture of methanol and ethanol is used as carbon source, and the temperature is kept for 30-35 min, then the product is taken out, the process first synthesizes tungsten carbide, cobalt and nano cerium dioxide composite phase, the nano defects on the surface due to plasma etching provide nucleation sites for the growth of graphene, the graphene sheet layer synthesized by the carbon source coats the composite phase, forming a wrinkled core-shell structure, the core layer composite phase provides basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film during friction, reducing the friction coefficient, and the composite phase is wrapped to reduce direct wear, the chemical inertness and dense structure of graphene also help to hinder the penetration of corrosive media, thus the tungsten-based hard alloy can significantly improve the bending strength, wear resistance and corrosion resistance, wherein the cerium dioxide nanoparticles are pinned in the tungsten carbide grain boundary and cobalt binder phase, not only forming a semi-coherent interface, increasing the interface binding energy, making the crack propagation consume additional energy, but also inhibiting grain growth at high temperature, playing a grain refinement and composite phase strengthening role, and the cerium dioxide nanoparticles effectively fill the pores of tungsten carbide-cobalt, blocking the corrosion channel, furthermore, the oxygen vacancies of cerium dioxide promote the cracking of carbon source, making the coverage of graphene more uniform, the cerium dioxide nanoparticles can prevent the slip of the graphene shell layer during sintering, improving the stability of the coating layer, and the graphene-coated core-shell composite powder is obtained; S2, the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder in step S1 are uniformly mixed by wet ball milling, and in the ball milling process, the ratio of material to ball is 5:1, the rotation speed is 200-250 rpm, the time is 3-4 h, vacuum drying at 60 DEG C, placing in a mold and pressing into a green body under 300 MPa, the green body is placed in a pyrophyllite mold, a six-surface pressing machine is used for high temperature and high pressure sintering, and argon is introduced for protection, first heated to 800 DEG C for 1-2 min, then heated to 1100-1200 DEG C, the sintering pressure is fixed at 3-5 GPa, the holding time is 4-8 min, the sample is taken out, polished, the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder form a physical anchoring effect through mechanical interlocking, and the C=O, C-OH and other dangling bonds at the edge of the graphene can react with tungsten carbide or cobalt to form W-C or Co-C bonds, enhance the interface bonding, the external stress is effectively transmitted through the interface, avoiding local stress concentration, improving the bending strength, at the same time, also further enhancing the chemical inert barrier protection effect, fully isolating the corrosion medium, enhancing the corrosion resistance, and the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder synergistically construct a multi-scale lubrication system, reduce material wear, and obtain a high corrosion and wear resistant tungsten-based hard alloy; Preferably, in step S1, the volume ratio of methanol and ethanol in the mixed carbon source of methanol and ethanol is 3-4:1, and by adjusting the flow of the carbon source, 2-5 layers of graphene are ensured to be generated, which is beneficial to the interface bonding.

[0009] The beneficial effects obtained by the present application are as follows: The application enhances the interface bonding of the two by physical anchoring and chemical bonding in the way of high-temperature sintering of tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber and graphene-coated core-shell composite powder, reduces defects, not only effectively transmits external stress, but also strengthens the barrier protection effect, fully isolates the infiltration of corrosive media, also constructs a multi-scale lubrication system, reduces the wear of tungsten carbide and cobalt and the like, thereby significantly enhances the bending strength, corrosion resistance and wear resistance, optimizes the use performance of tungsten-based hard alloy and prolongs its use cycle; in the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber, copper-nickel bimetallic MOF nanoparticles, ammonium metatungstate and polyvinylpyrrolidone are used as the precursor spinning solution, tungsten-based composite oxide nanofiber is prepared first, then a molybdenum disulfide coating layer is generated on the surface of the tungsten-based composite oxide nanofiber through a hydrothermal sulfuration reaction, the surface toughness is endowed, a rigid-flexible fiber structure is formed, finally, boron nitride is anchored on the surface of the molybdenum disulfide through the Dow Corning Z-6020 silane coupling agent, the double amino functional groups form Si-O-W / Mo covalent bonds and hydrogen bonds with the oxygen vacancies and sulfur vacancies on the surface of the fiber, the interface bonding strength is enhanced, the fiber surface defects are filled, the bending strength is improved by reducing stress concentration, the lubricity of molybdenum disulfide and the hardness of boron nitride synergistically act, the fiber core is protected from being worn, at the same time, the dense barrier formed by molybdenum disulfide and boron nitride effectively reduces the infiltration of corrosive media; in the graphene-coated core-shell composite powder, tungsten carbide, cobalt and nanometer cerium dioxide composite phases are used as the core, and the graphene sheet layers in-situ grown on the surface thereof are used as the shell layer, a wrinkled core-shell structure is formed, the core layer composite phase provides basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film in the friction process, reduces the friction coefficient, and the composite phase wrapped by the graphene reduces direct wear, the chemical inertness and dense structure of the graphene are also conducive to hindering the infiltration of corrosive media; the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder are used to prepare a high-corrosion-resistant and wear-resistant tungsten-based hard alloy, which effectively enhances the bending strength, corrosion resistance and wear resistance and optimizes the use performance of the material. BRIEF DESCRIPTION OF DRAWINGS

[0010] Figure 1 The bending fracture scanning electron microscope image of the high-corrosion-resistant and wear-resistant tungsten-based hard alloy prepared in Example 1 of the application; Figure 2 The bending strength result graph of Examples 1-4 and Comparative Examples 1-3 of the application; Figure 3 The volume wear rate result graph of Examples 1-4 and Comparative Examples 1-3 of the application; Figure 4 The mass loss rate result graph of Examples 1-4 and Comparative Examples 1-3 of the application. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments of the present application; based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the present application.

[0012] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as is commonly understood by one of ordinary skill in the art. In addition, any method and material similar or equivalent to those described herein can be used in the present application. The preferred methods and materials described herein are only for illustration and cannot limit the content of the present application.

[0013] The experimental methods in the following embodiments are all conventional methods unless otherwise specified; the experimental materials used in the following embodiments are all purchased from commercial channels unless otherwise specified. Embodiment

[0014] The embodiment provides a high-corrosion-resistance and wear-resistance tungsten-based hard alloy, which comprises the following components in parts by weight: tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber 30 parts, and graphene-coated core-shell composite powder 90 parts.

[0015] The tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber is prepared from the following components in parts by weight: copper-nickel bimetallic MOF nanoparticles 6 parts, ammonium metatungstate 20 parts, polyvinylpyrrolidone 10 parts, sodium molybdate dihydrate 5 parts, thiourea 8 parts, boron nitride 1 part, and Dow Corning Z-6020 silane coupling agent 5 parts.

[0016] The graphene-coated core-shell composite powder is a core-shell structure powder obtained by subjecting tungsten carbide powder, cobalt powder and nanometer cerium dioxide powder to ball milling, plasma activation treatment, and then growing a graphene coating layer on the surface in situ.

[0017] The preparation method of the tungsten-based composite oxide@molybdenum disulfide-boron nitride hybrid nanofiber specifically comprises the following steps: (1) 1.2 g of copper nitrate trihydrate and 0.6 g of nickel nitrate hexahydrate were dissolved in 15 mL of deionized water, stirred for 1 h to form solution I for standby, 1.0 g of trimesic acid was dissolved in 25 mL of anhydrous ethanol, stirred for 1 h to form solution II for standby, then solution I and solution II were mixed, 0.4 g of polyvinylpyrrolidone was added, stirred uniformly, and placed in a reaction kettle at 120°C for 12 h of hydrothermal reaction, the product was washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum, the copper ions, nickel ions and trimesic acid were combined by coordination bond to form a bimetallic three-dimensional porous framework structure, the porous structure and high specific surface area helped the uniform dispersion of tungsten species in the subsequent process, avoiding particle agglomeration in the calcination process, and copper-nickel bimetallic MOF nanoparticles were obtained; (2) The copper-nickel bimetallic MOF nanoparticles in step (1) were dispersed in 6 mL of N,N-dimethylformamide solvent, ultrasonicated for 50 min, then ammonium metatungstate and polyvinylpyrrolidone were added, the amount of ammonium metatungstate was 2.0 g, and the amount of polyvinylpyrrolidone was 1.0 g, ammonium metatungstate was calcined and decomposed to generate tungsten trioxide as the main phase material, which provided a rigid skeleton for the fiber to resist deformation under external force, and polyvinylpyrrolidone acted as a polymer template to form a uniform precursor with ammonium metatungstate and copper-nickel bimetallic MOF nanoparticles, ensuring continuous and uniform fibers during electrospinning, polyvinylpyrrolidone was thermally decomposed to form pores, which improved the toughness of the fiber and relieved stress concentration, thereby enhancing the bending strength, and the precursor spinning solution was obtained after stirring for 30 min. Electrospinning technology was used, the voltage was set to 18 kV, the pushing rate was 0.05 mm / s, and the collected fiber was placed in a crucible, dried at 60°C for 2 h, and then calcined in air at a heating rate of 1°C / min to 550°C for 2 h. The precursor spinning solution was stretched into a fiber under a high-voltage electric field, and a continuous and uniform, porous nanofiber grid structure was formed after calcination, wherein copper oxide, nickel oxide and part of tungsten trioxide generated by thermal decomposition of copper-nickel bimetallic MOF nanoparticles reacted to form CuWO4 / NiWO4 composite oxides with high hardness and chemical inertness, which enhanced the wear resistance and corrosion resistance, and at the same time, CuWO4 / NiWO4 composite oxides and unreacted tungsten trioxide together composed the rigid structure of the fiber, which effectively resisted deformation and loss during the wear and corrosion process, and tungsten-based composite oxide nanofibers were obtained; (3) sodium molybdate dihydrate and thiourea are dissolved in 30 mL of deionized water, the added amount of sodium molybdate dihydrate and thiourea is 0.5 g and 0.8 g respectively, sodium molybdate dihydrate and thiourea respectively provide a molybdenum source and a sulfur source, which can form a molybdenum disulfide coating layer, sufficient thiourea can reduce the sulfur vacancies in the molybdenum disulfide, avoid defects from becoming corrosion initiation points, and also can enhance the interface bonding between the molybdenum disulfide and the fiber, improve the wear resistance, then the tungsten-based composite oxide nanofiber in step (2) is added, ultrasonic dispersion is performed for 20 min, the pH is adjusted to 4.0, and then reaction is performed at 200°C for 12 h, the product is washed with an 80% ethanol solution for 5 times, vacuum dried at 60°C, and then annealed in a 2% hydrogen and 98% argon atmosphere at 400°C for 2 h, a molybdenum disulfide coating layer is formed on the surface of the tungsten-based composite oxide nanofiber through a hydrothermal sulfidation reaction, which endows the surface with toughness characteristics, forming a fiber structure with rigidity and flexibility, the molybdenum disulfide and the oxygen vacancies on the surface of the tungsten-based composite oxide nanofiber form Mo-O-W covalent bonds, enhancing the interface bonding force and reducing stress concentration, the layered structure of the molybdenum disulfide can slip when stressed, absorbing part of the mechanical energy and avoiding brittle fracture of the fiber, enhancing the bending strength, the interlayer shear strength of the molybdenum disulfide is low, which can reduce the friction coefficient and surface wear, and at the same time, a protective film is formed on the material surface during friction, avoiding direct contact with the fiber core, and in addition, the molybdenum disulfide can form a passivation layer in a humid environment, blocking the penetration of corrosion medium, obtaining a tungsten-based composite oxide@molybdenum disulfide nanofiber; (4) 0.1 g of boron nitride is dispersed in 20 mL of a 90% ethanol solution, 0.5 mL of Dow Corning Z-6020 silane coupling agent is added, the grade of the Dow Corning Z-6020 silane coupling agent is OFS-6020, the Dow Corning Z-6020 silane coupling agent contains a diamino functional group, which can form stronger hydrogen bonds and covalent bonds with molybdenum disulfide and boron nitride, reducing interface defects and thus reducing the risk of wear and tear, ultrasonic treatment is performed for 50 min, obtaining a boron nitride suspension for use, then the tungsten-based composite oxide@molybdenum disulfide nanofiber in step (3) is immersed in the boron nitride suspension, stirring at 60°C for 2 h, vacuum drying at 80°C, and finally annealing at 320°C for 1 h, the boron nitride is anchored on the surface of the molybdenum disulfide through the Dow Corning Z-6020 silane coupling agent, forming a coating and modification layer on the tungsten-based composite oxide nanofiber, the diamino functional group forms Si-O-W / Mo covalent bonds and hydrogen bonds with the oxygen vacancies and sulfur vacancies on the surface of the fiber, significantly enhancing the interface bonding strength, filling the surface defects of the fiber and improving the bending strength by reducing stress concentration, the lubricity of the molybdenum disulfide and the hard characteristics of the boron nitride synergistically protect the fiber core from wear, in addition, the dense barrier formed by the molybdenum disulfide and the boron nitride effectively reduces the penetration of corrosion medium, among them, the hydrophobicity and chemical inertness of the boron nitride can block the contact between the corrosion medium and the fiber matrix, obtaining a tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber.

[0018] The embodiment provides a preparation method of a high-corrosion-resistance and wear-resistance tungsten-based hard alloy, and specifically comprises the following steps. S1, tungsten carbide powder, cobalt powder and nanometer cerium dioxide powder are sequentially loaded into a ball mill jar according to a mass ratio of 10:3:2, a ball-to-powder ratio of 5:1, and 1.0% of the total mass of the powders is added with stearic acid, and then the powders are ball milled at a speed of 200 rpm for 10 h, and then the speed is adjusted to 310 rpm for interval ball milling for 2 h, in the interval ball milling process, the ball milling is performed for 30 min, and then the ball milling is paused for 10 min, and then the powders are dry mixed at a speed of 300 rpm for 4 h, and high-purity argon gas is used as a protective atmosphere, the obtained mixed powders are subjected to hydrogen plasma treatment at a power of 120 W for 30 min, finally, the mixed powders after the plasma treatment are placed into a porcelain boat and pushed into a tube furnace, the porcelain boat is sealed, vacuumized and filled with nitrogen, the gas replacement is completed through repeating three times, the temperature is increased to 800 DEG C at a temperature increasing rate of 5 DEG C / min, a mixed carbon source of methanol and ethanol is introduced, the volume ratio of the methanol and the ethanol in the mixed carbon source is 4:1, the flow of the mixed carbon source is adjusted to ensure the generation of 2-5 layers of graphene, which is beneficial to the interface bonding, the temperature is kept for 35 min, and then the temperature is decreased to room temperature, and the product is taken out, in the process, the tungsten carbide, cobalt and nanometer cerium dioxide composite phase are synthesized first, the nanometer defects existing on the surface of the composite phase due to the plasma etching provide growth sites for the nucleation of graphene, the graphene sheet layer synthesized by the carbon source is wrapped around the composite phase, and a core-shell structure with an outer wrinkled shell is formed, the core layer of the composite phase provides a basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film in the friction process to reduce the friction coefficient, and the composite phase is wrapped to reduce direct wear, the chemical inertness and dense structure of the graphene are also beneficial to hindering the penetration of corrosion medium, and thus the tungsten-based hard alloy can significantly improve the bending strength, wear resistance and corrosion resistance, wherein, the cerium dioxide nanoparticles are pinned in the tungsten carbide grain boundary and the cobalt binder phase, not only form a semi-coherent interface, increase the interface bonding energy, make the crack propagation consume extra energy, but also inhibit the grain growth at high temperature, play a role in grain refinement and composite phase strengthening, and the cerium dioxide nanoparticles effectively fill the pores of the tungsten carbide-cobalt, block the corrosion channel, in addition, the oxygen vacancies of the cerium dioxide promote the cracking of the carbon source, the coverage of the graphene is more uniform, the cerium dioxide nanoparticles can prevent the slip of the graphene shell layer in the sintering process, improve the stability of the wrapped layer, and finally, the graphene-coated core-shell composite powder is obtained; S2, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder prepared in step S1 are uniformly mixed by wet ball milling, and in the ball milling process, the ratio of material to ball is 5:1, the rotation speed is 250 rpm, the time is 4 h, and the vacuum drying is carried out at 60℃, then the mixture is placed in a mold and pressed into a green body under a pressure of 300 MPa, the green body is placed in a pyrophyllite mold, a six-surface press is used for high-temperature and high-pressure sintering, and argon is introduced for protection, first heated to 800℃ for 2 min, then heated to 1200℃, the sintering pressure is fixed at 5GPa, and the holding time is 8 min, then the sample is taken out, polished, and the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder form a physical anchoring effect through mechanical interlocking, and the C=O, C-OH and other dangling bonds at the edges of the graphene react with tungsten carbide or cobalt to form W-C or Co-C bonds, thereby enhancing the interface bonding, effectively transmitting external stress through the interface to avoid local stress concentration, improving the bending strength, and further enhancing the chemical inert barrier protection effect, fully isolating the corrosion medium, and enhancing the corrosion resistance, and the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder cooperatively construct a multi-scale lubrication system to reduce material wear, thereby obtaining a high-corrosion-resistant and wear-resistant tungsten-based hard alloy.

[0019] In this embodiment, the bending fracture of the prepared high-corrosion-resistant and wear-resistant tungsten-based hard alloy is observed by scanning electron microscopy, and the micro-morphology is observed, Figure 1 The SEM image of the bending fracture of the high-corrosion-resistant and wear-resistant tungsten-based hard alloy prepared in Example 1 is enlarged 2000 times, as shown in Figure 1 The bending fracture of the high-corrosion-resistant and wear-resistant tungsten-based hard alloy prepared in this embodiment has the characteristics of regular shape and tight combination. Example

[0020] This embodiment proposes a high-corrosion-resistant and wear-resistant tungsten-based hard alloy, which comprises the following components by weight: 20 parts of tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, and 80 parts of graphene-coated core-shell composite powder.

[0021] The tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber is made of the following components by weight: 4 parts of copper-nickel bimetallic MOF nanoparticles, 10 parts of ammonium metatungstate, 8 parts of polyvinylpyrrolidone, 3 parts of sodium molybdate dihydrate, 6 parts of thiourea, 0.8 parts of boron nitride, and 4 parts of Dow Corning Z-6020 silane coupling agent.

[0022] The graphene-coated core-shell composite powder is a core-shell structure powder obtained by first ball milling, plasma activation treatment of tungsten carbide powder, cobalt powder and nanometer ceria powder, and then growing a graphene coating shell layer on the surface in situ.

[0023] The preparation method of the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber specifically comprises the following steps: (1) 1.0 g of copper nitrate trihydrate and 0.4 g of nickel nitrate hexahydrate are dissolved in 15 mL of deionized water, stirred for 0.5 h to form solution I for standby, 0.8 g of trimesic acid is dissolved in 25 mL of anhydrous ethanol, stirred for 0.5 h to form solution II for standby, then solution I and solution II are mixed, 0.2 g of polyvinylpyrrolidone is added, stirred uniformly, and placed in a reaction kettle at 110°C for 10 h of hydrothermal reaction, the product is washed with anhydrous ethanol for 3 times, and dried at 60°C under vacuum, the copper ions, nickel ions and trimesic acid are combined by coordination bond to form a bimetallic three-dimensional porous framework structure, the porous structure and high specific surface area thereof are helpful for uniform dispersion of tungsten species in the subsequent process, and particle agglomeration in the calcination process is avoided, thereby obtaining copper-nickel bimetallic MOF nanoparticles; (2) The copper-nickel bimetallic MOF nanoparticles in step (1) are dispersed in 6 mL of N,N-dimethylformamide solvent, ultrasonic treatment is performed for 30 min, then ammonium metatungstate and polyvinylpyrrolidone are added, the addition amount of ammonium metatungstate is 1.0 g, and the addition amount of polyvinylpyrrolidone is 0.8 g, the ammonium metatungstate is calcined and decomposed to generate tungsten trioxide as a main phase material, which provides a rigid skeleton for the fiber to resist deformation under external force, the polyvinylpyrrolidone acts as a polymer template to form a uniform precursor with the ammonium metatungstate and the copper-nickel bimetallic MOF nanoparticles, so as to ensure that the fiber is continuous and uniform during electrospinning, the polyvinylpyrrolidone is heat-decomposed to form pores, which improves the toughness of the fiber and relieves stress concentration, thereby enhancing the bending strength, stirring is performed for 20 min to obtain a precursor spinning solution, an electrospinning technology is adopted, a voltage of 10 kV is set, and a pushing rate of 0.03 mm / s is set, the collected fiber is placed in a crucible, dried at 50°C for 1 h, and then calcined in air at a heating rate of 1°C / min at 500°C for 1 h, the precursor spinning solution is stretched into a fiber under a high-voltage electric field, and a continuous and uniform porous nanofiber grid structure is formed after calcination, wherein copper oxide and nickel oxide generated by pyrolysis of the copper-nickel bimetallic MOF nanoparticles react with part of the tungsten trioxide to form CuWO4 / NiWO4 composite oxide, which has high hardness and chemical inertness, and enhances wear resistance and corrosion resistance, meanwhile, the CuWO4 / NiWO4 composite oxide and the unreacted tungsten trioxide together constitute a rigid structure of the fiber, which effectively resists deformation and loss in the process of wear and corrosion, thereby obtaining a tungsten-based composite oxide nanofiber; (3) 0.3 g of sodium molybdate dihydrate and 0.6 g of thiourea were dissolved in 30 mL of deionized water, and the sodium molybdate dihydrate and the thiourea were added in amounts of 0.3 g and 0.6 g, respectively, to provide a molybdenum source and a sulfur source, respectively, and a molybdenum disulfide coating layer was formed, sufficient thiourea could reduce the sulfur vacancies in the molybdenum disulfide, avoid defects from becoming corrosion initiation points, and also enhance the interfacial bonding between the molybdenum disulfide and the fiber and improve the wear resistance, then the tungsten-based composite oxide nanofiber of step (2) was added and ultrasonically dispersed for 10 min, the pH was adjusted to 4.0, and then the reaction was carried out at 180°C for 10 h, the product was washed with an 80% ethanol solution for 3 times, vacuum dried at 60°C, and then annealed at 350°C for 1 h in an atmosphere of 2% hydrogen and 98% argon, a molybdenum disulfide coating layer was formed on the surface of the tungsten-based composite oxide nanofiber by a hydrothermal sulfidation reaction, the surface was endowed with toughness, a fiber structure with rigidity and flexibility was formed, the molybdenum disulfide and the oxygen vacancies on the surface of the tungsten-based composite oxide nanofiber formed Mo-O-W covalent bonds, the interfacial bonding force was enhanced, stress concentration was reduced, the layered structure of the molybdenum disulfide could slip when stressed, part of the mechanical energy was absorbed, brittle fracture of the fiber was avoided, the bending strength was enhanced, the interlayer shear strength of the molybdenum disulfide was low, the friction coefficient could be reduced, surface wear was reduced, a protective film was formed on the material surface during friction, direct contact with the fiber core was avoided, and in addition, the molybdenum disulfide could form a passivation layer in a humid environment, penetration of corrosion media was blocked, and a tungsten-based composite oxide@molybdenum disulfide nanofiber was obtained; (4) 0.08 g of boron nitride was dispersed in 20 mL of a 90% ethanol solution, 0.4 mL of Dow Corning Z-6020 silane coupling agent was added, the grade of the Dow Corning Z-6020 silane coupling agent was OFS-6020, the Dow Corning Z-6020 silane coupling agent contained a diamino functional group, could form stronger hydrogen bonds and covalent bonds with the molybdenum disulfide and the boron nitride, reduce interfacial defects, and thus reduce the risk of wear and tear, ultrasonic treatment was carried out for 40 min, a boron nitride suspension was obtained and was ready for use, then the tungsten-based composite oxide@molybdenum disulfide nanofiber of step (3) was immersed in the boron nitride suspension, stirring was carried out at 50°C for 1 h, vacuum drying was carried out at 80°C, and finally annealing treatment was carried out at 300°C for 0.5 h, the boron nitride was anchored on the surface of the molybdenum disulfide through the Dow Corning Z-6020 silane coupling agent, formed a coating and modification layer on the tungsten-based composite oxide nanofiber, the diamino functional group formed Si-O-W / Mo covalent bonds and hydrogen bonds with the oxygen vacancies and the sulfur vacancies on the surface of the fiber, the interfacial bonding strength was significantly enhanced, the fiber surface defects were filled, the bending strength was improved by reducing stress concentration, the lubricity of the molybdenum disulfide and the hard property of the boron nitride synergistically protected the fiber core from being worn, in addition, a dense barrier was formed by the molybdenum disulfide and the boron nitride, penetration of corrosion media was effectively reduced, the hydrophobicity and chemical inertness of the boron nitride could block the contact between the corrosion media and the fiber matrix, and a tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber was obtained.

[0024] The embodiment provides a preparation method of a high-corrosion-resistance and wear-resistance tungsten-based hard alloy, and specifically comprises the following steps. S1, tungsten carbide powder, cobalt powder and nanometer cerium dioxide powder are sequentially loaded into a ball mill jar according to a mass ratio of 10:3:1, a ball-to-powder ratio is 5:1, 0.8% of the total mass of the powders is added as stearic acid, ball milling is first performed at a speed of 180 rpm for 8h, then the speed is adjusted to 280 rpm for interval ball milling for 1h, in the interval ball milling process, ball milling is performed for 30 min, then the process is paused for 10 min, and then dry mixing is performed at a speed of 300 rpm for 3h, high-purity argon gas is used as a protective atmosphere, the obtained mixed powder is subjected to hydrogen plasma treatment at a power of 80 W for 10 min, finally, the mixed powder after the plasma treatment is placed into a porcelain boat and pushed into a tube furnace, the porcelain boat is sealed, vacuumized and filled with nitrogen, gas replacement is completed for three times, the temperature is increased to 750 DEG C at a temperature increasing rate of 5 DEG C / min, a mixed carbon source of methanol and ethanol is introduced, the volume ratio of methanol and ethanol in the mixed carbon source is 3:1, the carbon source flow is adjusted to ensure the generation of 2-5 layers of graphene, which is beneficial to interface bonding, the temperature is kept for 30 min, and then the temperature is decreased to room temperature, and the product is taken out, in the process, tungsten carbide, cobalt and nanometer cerium dioxide composite phases are first synthesized, nanometer defects existing on the surface of the composite phases due to plasma etching provide growth sites for the nucleation of graphene, and the graphene sheet layers synthesized by the carbon source wrap the composite phases, forming a core-shell structure with wrinkles on the outer layer, the core layer of the composite phases provides basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film in the friction process to reduce the friction coefficient, and the composite phases are wrapped to reduce direct wear, the chemical inertness and dense structure of the graphene are also beneficial to hindering the penetration of corrosion media, and thus the tungsten-based hard alloy can significantly improve the bending strength, wear resistance and corrosion resistance, wherein, the cerium dioxide nanoparticles are pinned in the tungsten carbide grain boundaries and the cobalt binder phase, not only form a semi-coherent interface, increase the interface bonding energy, make the crack propagation consume extra energy, but also inhibit the grain growth at high temperatures, play a grain refinement and composite phase strengthening role, and the cerium dioxide nanoparticles effectively fill the pores of the tungsten carbide-cobalt, block the corrosion channels, furthermore, the oxygen vacancies of the cerium dioxide promote the cracking of the carbon source, make the coverage of the graphene more uniform, the cerium dioxide nanoparticles can prevent the slip of the graphene shell layer in the sintering process, improve the stability of the coating layer, and finally, the graphene-coated core-shell composite powder is obtained; S2, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, the graphene coated core-shell composite powder of step S1 is mixed uniformly by wet ball milling, in the ball milling process, the ratio of material to ball is 5:1, the rotation speed is 200 rpm, the time is 3h, 60℃ vacuum drying, placed in the mold, pressed into a green body under 300MPa, the green body is placed in the pyrophyllite mold, a six-surface press is used for high temperature and high pressure sintering, and argon is introduced for protection, first heated to 800℃ for 1min, then heated to 1100℃, the sintering pressure is fixed at 3GPa, the holding time is 4min, the sample is taken out, polished, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder form a physical anchoring effect through mechanical interlocking, and the C=O, C-OH and other dangling bonds at the edge of graphene can react with tungsten carbide or cobalt to form W-C or Co-C bonds, enhancing the interface bonding, effectively transmitting external stress through the interface to avoid local stress concentration, improving the bending strength, and also further enhancing the chemical inert barrier protection effect, fully isolating the corrosion medium, enhancing the corrosion resistance, and the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder synergistically construct a multi-scale lubrication system, reducing material wear, and obtaining a high corrosion and wear resistant tungsten-based hard alloy. Embodiment

[0025] The embodiment provides a high corrosion and wear resistant tungsten-based hard alloy, which comprises the following components in parts by weight: 25 parts of tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, and 85 parts of graphene coated core-shell composite powder.

[0026] The tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber is prepared from the following components in parts by weight: 5 parts of copper-nickel bimetallic MOF nanoparticles, 15 parts of ammonium metatungstate, 9 parts of polyvinylpyrrolidone, 4 parts of sodium molybdate dihydrate, 7 parts of thiourea, 0.9 parts of boron nitride and 4.5 parts of Dow Corning Z-6020 silane coupling agent.

[0027] The graphene coated core-shell composite powder is a core-shell structure powder obtained by first ball milling, plasma activation treatment of tungsten carbide powder, cobalt powder and nanometer ceria powder, and then growing a graphene coating shell layer in situ on the surface.

[0028] The preparation method of the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber comprises the following steps: (1) Dissolve 1.1g of copper nitrate trihydrate and 0.5g of nickel nitrate hexahydrate in 15mL of deionized water and stir for 0.75h to form solution I for later use. Then dissolve 0.9g of trimesic acid in 25mL of anhydrous ethanol and stir for 0.75h to form solution II for later use. Then mix solution I and solution II and add 0.3g of polyvinylpyrrolidone. Stir evenly and place in a reaction vessel at 115℃ for 11h of hydrothermal reaction. Wash the product with anhydrous ethanol 4 times and vacuum dry at 60℃. Copper ions, nickel ions and trimesic acid are combined through coordinate bonds to form a bimetallic three-dimensional porous framework structure. Its porous structure and high specific surface area help to uniformly disperse tungsten species in the subsequent process and avoid particle agglomeration during calcination to obtain copper-nickel bimetallic MOF nanoparticles. (2) The copper-nickel bimetallic MOF nanoparticles described in step (1) were dispersed in 6 mL of N,N-dimethylformamide solvent and sonicated for 40 min. Then, ammonium metatungstate and polyvinylpyrrolidone were added. The amount of ammonium metatungstate added was 1.5 g and the amount of polyvinylpyrrolidone added was 0.9 g. The ammonium metatungstate was calcined and decomposed to generate tungsten trioxide as the main phase, which provided a rigid skeleton for the fiber and resisted deformation by external force. Polyvinylpyrrolidone, as a polymer template, formed a uniform precursor with ammonium metatungstate and copper-nickel bimetallic MOF nanoparticles, ensuring that the fiber was continuous and uniform during electrospinning. The thermal decomposition of polyvinylpyrrolidone created pores, which improved the toughness of the fiber and relieved stress concentration, thereby enhancing the bending strength. After stirring for 25 min, the precursor spinning solution was obtained. Electrospinning technology was used, and the voltage was set to 1. At 4kV and a propulsion rate of 0.04mm / s, the collected fibers were placed in a crucible and dried at 55℃ for 1.5h. Then, they were calcined in air at 525℃ with a heating rate of 1℃ / min for 1.5h. The precursor spinning solution was stretched into fibers under a high-voltage electric field. After calcination, a continuous, uniform, and porous nanofiber network structure was formed. Among them, copper oxide and nickel oxide generated by the pyrolysis of copper-nickel bimetallic MOF nanoparticles reacted with some tungsten trioxide to form CuWO4 / NiWO4 composite oxide, which has high hardness and chemical inertness, enhancing wear resistance and corrosion resistance. At the same time, CuWO4 / NiWO4 composite oxide and unreacted tungsten trioxide together formed the rigid structure of the fiber, which effectively resisted deformation and loss during wear and corrosion, thus obtaining tungsten-based composite oxide nanofibers. (3) sodium molybdate dihydrate and thiourea are dissolved in 30 mL of deionized water, the amount of sodium molybdate dihydrate and thiourea added is 0.4 g and 0.7 g respectively, the sodium molybdate dihydrate and thiourea respectively provide a molybdenum source and a sulfur source, which can form a molybdenum disulfide coating layer, sufficient thiourea can reduce the sulfur vacancies in the molybdenum disulfide, avoid defects from becoming corrosion initiation points, and also can enhance the interface bonding between the molybdenum disulfide and the fiber, improve the wear resistance, then the tungsten-based composite oxide nanofiber of step (2) is added, ultrasonic dispersion is performed for 15 min, the pH is adjusted to 4.0, then reaction is performed at 190°C for 11 h, the product is washed with an 80% ethanol solution for 4 times, vacuum dried at 60°C, then placed in a 2% hydrogen and 98% argon atmosphere and annealed at 375°C for 1.5 h, through a hydrothermal sulfurization reaction, a molybdenum disulfide coating layer is formed on the surface of the tungsten-based composite oxide nanofiber, which gives the surface a toughness characteristic, forming a fiber structure with rigidity and flexibility, the molybdenum disulfide and the oxygen vacancies on the surface of the tungsten-based composite oxide nanofiber form Mo-O-W covalent bonds, which enhances the interface bonding force, reduces stress concentration, the layered structure of the molybdenum disulfide can slip when stressed, absorbs part of the mechanical energy, avoids brittle fracture of the fiber, enhances the bending strength, the interlayer shear strength of the molybdenum disulfide is low, which can reduce the friction coefficient and reduce surface wear, at the same time, a protective film is formed on the surface of the material during friction, which avoids direct contact with the fiber core, and the molybdenum disulfide can form a passivation layer in a humid environment, which blocks the penetration of corrosion medium, obtaining a tungsten-based composite oxide@molybdenum disulfide nanofiber; (4) 0.09 g boron nitride is dispersed in 20 mL of 90% ethanol solution, 0.45 mL of Dow Corning Z-6020 silane coupling agent is added, the grade of Dow Corning Z-6020 silane coupling agent is OFS-6020, the Dow Corning Z-6020 silane coupling agent contains a diamino functional group, which can form stronger hydrogen bonds and covalent bonds with molybdenum disulfide and boron nitride, reduce interface defects, thereby reducing the risk of wear and tear, ultrasonic treatment for 45 min, to obtain a boron nitride suspension for use, then the tungsten-based composite oxide@molybdenum disulfide nanofiber described in step (3) is immersed in the boron nitride suspension, stirred at 55°C for 1.5 h, vacuum dried at 80°C, and finally annealed at 310°C for 0.75 h. Boron nitride is anchored on the surface of molybdenum disulfide through Dow Corning Z-6020 silane coupling agent, forming a coating and modification layer on the tungsten-based composite oxide nanofiber. The diamino functional group forms Si-O-W / Mo covalent bonds and hydrogen bonds with the oxygen vacancies and sulfur vacancies on the surface of the fiber, significantly enhancing the interface bonding strength, filling the surface defects of the fiber, reducing stress concentration and improving the bending strength. The lubricity of molybdenum disulfide and the hard characteristics of boron nitride synergistically protect the fiber core from wear. Furthermore, the dense barrier formed by molybdenum disulfide and boron nitride effectively reduces the penetration of corrosive media. The hydrophobicity and chemical inertness of boron nitride can block the contact between corrosive media and the fiber matrix, resulting in tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber.

[0029] The embodiment provides a preparation method of high-corrosion-resistant and wear-resistant tungsten-based hard alloy, and specifically comprises the following steps: S1, the tungsten carbide powder, cobalt powder, nano cerium dioxide powder according to the mass ratio 10:3:1.5 is loaded into the ball mill jar in turn, the ball to powder ratio is 5:1, then 0.9% of the total mass of the powder is added into stearic acid, first ball milling at 190 rpm for 9h, then the speed is adjusted to 295 rpm for 1.5h, during the interval ball milling, ball milling for 30min, pause for 10min, then dry mixing at 300rpm for 3.5h, and high-purity argon is used as the protective atmosphere, the mixed powder obtained is treated by hydrogen plasma, the power is 100W, the time is 20min, finally the mixed powder after plasma treatment is put into a porcelain boat and pushed into a tube furnace, sealed, vacuumed and filled with nitrogen, the gas replacement is completed for three times, the temperature is raised to 775℃ at a rate of 5℃ / min, the mixed carbon source of methanol and ethanol is introduced, the volume ratio of methanol and ethanol in the mixed carbon source is 3.5:1, by adjusting the flow of carbon source, 2-5 layers of graphene are generated, which is beneficial to interface bonding, the temperature is kept for 32.5min, and then the temperature is lowered to room temperature, and the product is taken out, the process first synthesizes tungsten carbide, cobalt and nano cerium dioxide composite phase, the nano defects on the surface of the composite phase due to plasma etching provide growth sites for graphene nucleation, the graphene sheet layer synthesized by the carbon source coats the composite phase, forming a wrinkled core-shell structure, the core layer of the composite phase provides basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film during friction, reducing the friction coefficient, and the composite phase is wrapped, reducing direct wear, the chemical inertness and dense structure of graphene also help to hinder the penetration of corrosive media, so that the tungsten-based hard alloy can significantly improve the bending strength, wear resistance and corrosion resistance, wherein, the cerium dioxide nanoparticles are pinned in the tungsten carbide grain boundary and cobalt binder phase, not only forming a semi-coherent interface, increasing the interface bonding energy, making the crack propagation consume additional energy, but also inhibiting grain growth at high temperature, playing a grain refinement and composite phase strengthening role, and the cerium dioxide nanoparticles effectively fill the pores of tungsten carbide-cobalt, block the corrosion channel, in addition, the oxygen vacancies of cerium dioxide promote the cracking of carbon source, making the coverage of graphene more uniform, the cerium dioxide nanoparticles can prevent the slip of the graphene shell layer during sintering, improve the stability of the coating layer, and obtain a graphene-coated core-shell composite powder; S2, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, the graphene coated core-shell composite powder of step S1 is mixed uniformly by wet ball milling, in the ball milling process, the ratio of material to ball is 5:1, the rotation speed is 225 rpm, the time is 3.5 h, vacuum drying at 60℃, placing in the mold and pressing into a green body under 300 MPa, the green body is placed in a pyrophyllite mold, a six-surface press is used for high-temperature and high-pressure sintering, and argon is introduced for protection, first heated to 800℃ for 1.5 min, then heated to 1150℃, the sintering pressure is fixed at 4GPa, the holding time is 6 min, the sample is taken out, polished, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder form a physical anchoring effect through mechanical interlocking, and the C=O, C-OH and other dangling bonds at the edge of the graphene can react with tungsten carbide or cobalt to form W-C or Co-C bonds, enhancing the interface bonding, effectively transmitting external stress through the interface to avoid local stress concentration, improving the bending strength, and also further enhancing the chemical inert barrier protection effect, fully isolating the corrosion medium, enhancing the corrosion resistance, and the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder synergistically construct a multi-scale lubrication system, reducing material wear, and obtaining a high corrosion and wear resistant tungsten-based hard alloy. Embodiment

[0030] The embodiment provides a high corrosion and wear resistant tungsten-based hard alloy, which comprises the following components in parts by weight: 30 parts of tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and 80 parts of graphene coated core-shell composite powder.

[0031] The tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber is made of the following components in parts by weight: 6 parts of copper-nickel bimetallic MOF nanoparticles, 20 parts of ammonium metatungstate, 10 parts of polyvinylpyrrolidone, 3 parts of sodium molybdate dihydrate, 6 parts of thiourea, 0.8 parts of boron nitride and 4 parts of Dow Corning Z-6020 silane coupling agent.

[0032] The graphene coated core-shell composite powder is a core-shell structure powder obtained by first ball milling, plasma activation treatment of tungsten carbide powder, cobalt powder and nanometer ceria powder, and then growing a graphene coating shell layer in situ on the surface.

[0033] The preparation method of the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber specifically comprises the following steps: (1) 1.2 g of copper nitrate trihydrate and 0.6 g of nickel nitrate hexahydrate were dissolved in 15 mL of deionized water, stirred for 0.5 h to form solution I for standby, 1.0 g of trimesic acid was dissolved in 25 mL of anhydrous ethanol, stirred for 0.5 h to form solution II for standby, then solution I and solution II were mixed, 0.4 g of polyvinylpyrrolidone was added, stirred uniformly, and placed in a reaction kettle at 120°C for 10 h of hydrothermal reaction, the product was washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum, the copper ions, nickel ions and trimesic acid were combined by coordination bond to form a bimetallic three-dimensional porous framework structure, the porous structure and high specific surface area helped the uniform dispersion of subsequent tungsten species, avoiding particle agglomeration during calcination, and copper-nickel bimetallic MOF nanoparticles were obtained; (2) The copper-nickel bimetallic MOF nanoparticles in step (1) were dispersed in 6 mL of N,N-dimethylformamide solvent, ultrasonicated for 30 min, then ammonium metatungstate and polyvinylpyrrolidone were added, the amount of ammonium metatungstate added was 2.0 g, and the amount of polyvinylpyrrolidone added was 1.0 g, ammonium metatungstate was calcined and decomposed to generate tungsten trioxide as the main phase material, which provided a rigid skeleton for the fiber to resist deformation under external force, and polyvinylpyrrolidone acted as a polymer template to form a uniform precursor with ammonium metatungstate and copper-nickel bimetallic MOF nanoparticles, ensuring continuous and uniform fibers during electrospinning, and polyvinylpyrrolidone was thermally decomposed to create pores, which improved the toughness of the fiber and relieved stress concentration, thereby enhancing the bending strength, and the precursor spinning solution was obtained after stirring for 20 min, electrospinning technology was used, the voltage was set to 18 kV, the pushing rate was 0.05 mm / s, the collected fiber was placed in a crucible, dried at 60°C for 1 h, and then calcined in air at a heating rate of 1°C / min to 550°C for 1 h, the precursor spinning solution was stretched into a fiber under a high-voltage electric field, and a continuous and uniform, porous nanofiber grid structure was formed after calcination, wherein copper oxide and nickel oxide generated by thermal decomposition of copper-nickel bimetallic MOF nanoparticles reacted with part of tungsten trioxide to form CuWO4 / NiWO4 composite oxides with high hardness and chemical inertness, which enhanced wear resistance and corrosion resistance, and the CuWO4 / NiWO4 composite oxides and unreacted tungsten trioxide together composed the rigid structure of the fiber, effectively resisting deformation and loss during the wear and corrosion process, and tungsten-based composite oxide nanofibers were obtained; (3) 0.3 g of sodium molybdate dihydrate and 0.6 g of thiourea were dissolved in 30 mL of deionized water, and the sodium molybdate dihydrate and the thiourea were added in amounts of 0.3 g and 0.6 g, respectively, to provide a molybdenum source and a sulfur source, respectively, and a molybdenum disulfide coating layer was formed, sufficient thiourea could reduce the sulfur vacancies in the molybdenum disulfide, avoid defects from becoming corrosion initiation points, and also enhance the interfacial bonding between the molybdenum disulfide and the fiber and improve the wear resistance, then the tungsten-based composite oxide nanofiber of step (2) was added and ultrasonically dispersed for 10 min, the pH was adjusted to 4.0, and then the reaction was carried out at 200°C for 10 h, the product was washed with an 80% ethanol solution for 5 times, vacuum dried at 60°C, and then annealed at 400°C for 1 h in an atmosphere of 2% hydrogen and 98% argon, a molybdenum disulfide coating layer was formed on the surface of the tungsten-based composite oxide nanofiber by a hydrothermal sulfidation reaction, the surface was endowed with toughness, a fiber structure with rigidity and flexibility was formed, the molybdenum disulfide and the oxygen vacancies on the surface of the tungsten-based composite oxide nanofiber formed Mo-O-W covalent bonds, the interfacial bonding force was enhanced, stress concentration was reduced, the layered structure of the molybdenum disulfide could slip when stressed, part of the mechanical energy was absorbed, brittle fracture of the fiber was avoided, the bending strength was enhanced, the interlayer shear strength of the molybdenum disulfide was low, the friction coefficient could be reduced, surface wear was reduced, a protective film was formed on the surface of the material during friction to avoid direct contact with the fiber core, and in addition, the molybdenum disulfide could form a passivation layer in a humid environment to block the penetration of corrosion media, and a tungsten-based composite oxide@molybdenum disulfide nanofiber was obtained; (4) 0.08 g of boron nitride was dispersed in 20 mL of a 90% ethanol solution, 0.4 mL of Dow Corning Z-6020 silane coupling agent was added, the grade of the Dow Corning Z-6020 silane coupling agent was OFS-6020, the Dow Corning Z-6020 silane coupling agent contained a diamino functional group, could form stronger hydrogen bonds and covalent bonds with the molybdenum disulfide and the boron nitride, reduce interfacial defects, and thus reduce the risk of wear and tear, ultrasonic treatment was carried out for 40 min, a boron nitride suspension was obtained and was ready for use, then the tungsten-based composite oxide@molybdenum disulfide nanofiber of step (3) was immersed in the boron nitride suspension, stirring was carried out at 60°C for 1 h, vacuum drying was carried out at 80°C, and finally annealing treatment was carried out at 320°C for 0.5 h, the boron nitride was anchored on the surface of the molybdenum disulfide through the Dow Corning Z-6020 silane coupling agent, formed a coating and modification layer on the tungsten-based composite oxide nanofiber, the diamino functional group formed Si-O-W / Mo covalent bonds and hydrogen bonds with the oxygen vacancies and the sulfur vacancies on the surface of the fiber, the interfacial bonding strength was significantly enhanced, the fiber surface defects were filled, the bending strength was improved by reducing stress concentration, the lubricity of the molybdenum disulfide and the hard property of the boron nitride synergistically protected the fiber core from being worn, in addition, a dense barrier was formed by the molybdenum disulfide and the boron nitride, which effectively reduced the penetration of corrosion media, the hydrophobicity and chemical inertness of the boron nitride could block the contact between the corrosion media and the fiber matrix, and a tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber was obtained.

[0034] The embodiment provides a preparation method of a high-corrosion-resistance and wear-resistance tungsten-based hard alloy, and specifically comprises the following steps. S1, tungsten carbide powder, cobalt powder and nanometer cerium dioxide powder are sequentially loaded into a ball mill jar according to a mass ratio of 10:3:1, a ball-to-powder ratio is 5:1, 1.0% of the total mass of the powders is added into stearic acid, first ball milling is performed at a speed of 200 rpm for 8h, then the speed is adjusted to 310 rpm for interval ball milling for 1h, in the interval ball milling process, ball milling is performed for 30 min, then the process is paused for 10 min, then dry mixing is performed at a speed of 300 rpm for 3h, high-purity argon gas is used as a protective atmosphere, the obtained mixed powder is subjected to hydrogen plasma treatment, the power is 120 W, the time is 10 min, finally, the mixed powder after the plasma treatment is placed into a porcelain boat and pushed into a tube furnace, the porcelain boat is sealed, vacuumized and filled with nitrogen, the gas replacement is completed for three times, the temperature is increased to 800 DEG C at a temperature increasing rate of 5 DEG C / min, a mixed carbon source of methanol and ethanol is filled, the volume ratio of methanol and ethanol in the mixed carbon source is 4:1, the carbon source flow is adjusted to ensure the generation of 2-5 layers of graphene, which is beneficial to interface bonding, the temperature is kept for 30 min, and then the temperature is decreased to room temperature, and the product is taken out, in the process, tungsten carbide, cobalt and nanometer cerium dioxide composite phases are first synthesized, nanometer defects existing on the surface of the composite phases due to plasma etching provide growth sites for the nucleation of graphene, graphene sheets synthesized by the carbon source coat the composite phases, and a core-shell structure with an outer wrinkled shell is formed, the core layer of the composite phases provides basic hardness, the graphene shell layer prevents crack propagation through crack deflection and bridging effect, the graphene shell layer can also form a transfer film in the friction process to reduce the friction coefficient, and the composite phases are wrapped to reduce direct wear, the chemical inertness and dense structure of the graphene are also beneficial to hinder the penetration of corrosion medium, and thus the tungsten-based hard alloy can significantly improve the bending strength, wear resistance and corrosion resistance, wherein, the cerium dioxide nanoparticles are pinned in the tungsten carbide grain boundary and the cobalt binder phase, not only form a semi-coherent interface, increase the interface bonding energy, make the crack propagation consume extra energy, but also inhibit the grain growth at high temperature, play a grain refinement and composite phase strengthening role, and the cerium dioxide nanoparticles effectively fill the pores of the tungsten carbide-cobalt, block the corrosion channel, in addition, the oxygen vacancies of the cerium dioxide promote the cracking of the carbon source, make the coverage of the graphene more uniform, the cerium dioxide nanoparticles can prevent the slip of the graphene shell layer in the sintering process, improve the stability of the coating layer, and finally the graphene-coated core-shell composite powder is obtained; S2, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, the graphene coated core-shell composite powder of step S1 is uniformly mixed by wet ball milling, in the ball milling process, the ratio of material to ball is 5:1, the rotation speed is 250 rpm, the time is 3h, vacuum drying at 60℃, placing in the mold, pressing into green body under 300MPa, the green body is placed in the pyrophyllite mold, using a six-surface press for high temperature and high pressure sintering, and argon is introduced for protection, first heated to 800℃ for 1min, then to 1200℃, the sintering pressure is fixed at 5GPa, the holding time is 4min, the sample is taken out, polished, the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder form a physical anchoring effect through mechanical interlocking, and the C=O, C-OH and other dangling bonds at the edge of the graphene react with tungsten carbide or cobalt to form W-C or Co-C bonds, enhancing the interface bonding, the external stress is effectively transmitted through the interface, avoiding local stress concentration, improving the bending strength, at the same time, further enhancing the chemical inert barrier protection effect, fully isolating the corrosion medium, enhancing the corrosion resistance, and the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene coated core-shell composite powder synergistically construct a multi-scale lubrication system, reducing material wear, obtaining a high corrosion and wear resistant tungsten-based hard alloy.

[0035] Comparative Example 1 The present comparative example provides a high corrosion and wear resistant tungsten-based hard alloy, which is different from Example 1 in that the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber does not contain sodium molybdate dihydrate and thiourea; the preparation method of the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber does not include step (3); and the preparation method of the high corrosion and wear resistant tungsten-based hard alloy is the same as that of Example 1.

[0036] Comparative Example 2 The present comparative example provides a high corrosion and wear resistant tungsten-based hard alloy, which is different from Example 1 in that the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber does not contain boron nitride and Dow Corning Z-6020 silane coupling agent; the preparation method of the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber does not include step (4); and the preparation method of the high corrosion and wear resistant tungsten-based hard alloy is the same as that of Example 1.

[0037] Comparative Example 3 The present comparative example provides a high corrosion and wear resistant tungsten-based hard alloy, which is different from Example 1 in that the graphene coated core-shell composite powder does not contain nano ceria powder; the preparation method of the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber is the same as that of Example 1; and the preparation method of the high corrosion and wear resistant tungsten-based hard alloy does not add nano ceria powder in step S1.

[0038] Experimental Example 1 Mechanical property test Test samples: high corrosion and wear resistant tungsten-based hard alloys prepared from Examples 1-4 and Comparative Examples 1-3.

[0039] Test method: according to the standard GB / T6569-1986 standard, a universal material testing machine was used to test the bending strength of the test samples, the sample size was 3mm x 4mm x 35mm, the span was 30mm, and the loading speed was 0.5mm / min.

[0040] Figure 2 The bending strength results of Examples 1-4 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the bending strength of Examples 1-4 is 4206-4520MPa, indicating good bending strength; the bending strength of Comparative Examples 1-3 is 2685-3257MPa, indicating general bending strength; Comparative Example 1 does not contain sodium molybdate dihydrate and thiourea in the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber, which cannot generate a molybdenum disulfide coating layer on the surface of the tungsten-based composite oxide nanofiber, and cannot impart toughness characteristics, resulting in general bending strength; Comparative Example 2 does not contain boron nitride and Dow Corning Z-6020 silane coupling agent in the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofiber, which cannot anchor boron nitride on the surface of molybdenum disulfide, which is not conducive to filling the fiber surface defects, and thus cannot reduce stress concentration, resulting in general bending strength; Comparative Example 3 does not contain nanometer cerium dioxide powder in the graphene-coated core-shell composite powder, which cannot be pinned in the tungsten carbide grain boundary and cobalt binder phase to form a semi-coherent interface, making it easy for cracks to propagate, and also not conducive to preventing the slip of the graphene layer during sintering, limiting the crack deflection and bridging effect of graphene, resulting in general bending strength.

[0041] Experimental Example 2 Wear resistance experiment Test samples: high corrosion and wear resistant tungsten-based hard alloys prepared from Examples 1-4 and Comparative Examples 1-3.

[0042] Test method: the test samples were tested for wear resistance using a UMT-Tribolbab type ball-on-disc friction tester, a Si3N4 ball with a diameter of 6.35mm was used as the friction pair material, the load (F) was 10N, the rotation speed (R) was 364r / min, the rotation radius (d) was 3.5mm, the experimental time (T) was 60min, the total wear volume (Vm) of the sample was measured by an Alphastep P-7 probe contact profiler, and the volume wear rate (mm 3 / N·m) of the coating was calculated using the following formula: Volume wear rate (mm 3 / N·m) = Vm / (3.14 x F x d x R x T) Figure 3Volume wear rate results of Examples 1-4 and Comparative Examples 1-3; as shown in the figure, the volume wear rate of Examples 1-4 is 1.9-3.0 x 10 -5 mm 3 / N·m, indicating strong wear resistance; the volume wear rate of Comparative Examples 1-3 is 5.1-6.3 x 10 - 5 mm 3 / N·m, indicating weak wear resistance; Comparative Example 1 does not contain sodium molybdate dihydrate, thiourea in the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, which cannot generate a lubricating molybdenum disulfide coating layer, is not conducive to reducing the friction coefficient and reducing surface wear, and also does not help form a protective film on the material surface, increasing the risk of friction contact with the fiber core, resulting in weak wear resistance; Comparative Example 2 does not contain boron nitride, Dow Corning Z-6020 silane coupling agent in the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber, which cannot anchor boron nitride on the surface of molybdenum disulfide to play a hard feature, directly limiting the role of the hard phase, resulting in weak wear resistance; Comparative Example 3 does not contain nanometer cerium dioxide powder in the graphene-coated core-shell composite powder, which cannot play the role of grain refinement and composite phase strengthening, and is also not conducive to the stability of graphene coating, increasing the direct wear risk of the composite phase, resulting in weak wear resistance.

[0043] Experimental Example 3 Corrosion resistance experiment Test sample: high corrosion and wear resistant tungsten-based hard alloy prepared by Examples 1-4 and Comparative Examples 1-3.

[0044] Test method: the test sample was sequentially cleaned with acetone and anhydrous ethanol for 10 min, vacuum dried at 80°C for 2 h, cooled to room temperature, and the initial mass W0 (accurate to 0.01 mg) was recorded, and the surface area S (cm 2 ) of the sample was measured, then tested according to GB / T10125-2021, using a YWX / Q-150 type salt spray test chamber, preparing a 5% NaCl aqueous solution (adjusting pH to 7) as the corrosion solution, immersing the test sample completely in the corrosion solution, taking it out after 500 h, rinsing with deionized water, ultrasonic oscillation for 5 min, vacuum drying at 80°C for 2 h, cooling to room temperature, and recording the final mass W1 (accurate to 0.01 mg), and calculating the mass loss rate (mg / cm 2 ) according to the following formula: Mass loss rate (mg / cm 2 ) = (W0-W1) / S Figure 4 Mass loss rate results of Examples 1-4 and Comparative Examples 1-3; as shown in the figure, the mass loss rate of Examples 1-4 is 0.02-0.05 mg / cm 2, indicating that the corrosion resistance is better; the mass loss rate of Comparative Examples 1-3 is 0.12-0.18 mg / cm 2 , indicating that the corrosion resistance is general; the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber of Comparative Example 1 does not contain sodium molybdate dihydrate and thiourea, and cannot form a passivation layer through molybdenum disulfide, which is not conducive to blocking the penetration of corrosive media, resulting in general corrosion resistance; the tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber of Comparative Example 2 does not contain boron nitride, and does not contain Dow Corning Z-6020 silane coupling agent, which cannot anchor boron nitride on the surface of molybdenum disulfide to form a dense barrier, which is not conducive to reducing the penetration of corrosive media, resulting in general corrosion resistance; the graphene-coated core-shell composite powder of Comparative Example 3 does not contain nanometer cerium dioxide powder, which cannot fill the pores of tungsten carbide-cobalt to block the corrosion channel, and is also not conducive to uniform and stable coating of graphene, which limits the barrier effect of graphene on corrosive media, resulting in general corrosion resistance.

[0045] The above experimental results show that the mechanical properties, wear resistance and corrosion resistance of Examples 1-4 of the present application are significantly better than those of Comparative Examples 1-3, wherein the bending strength, wear resistance and corrosion resistance of Example 1 using tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and graphene-coated core-shell composite powder are better, stronger and better, respectively. The tungsten-based composite oxide @ molybdenum disulfide boron nitride hybrid nanofiber and the graphene-coated core-shell composite powder are sintered at high temperature to enhance the interfacial bonding of the two in a physical anchoring and chemical bonding manner, reduce defects, not only effectively transfer external stress, but also strengthen the barrier protection effect, fully isolate the penetration of corrosive media, and also build a multi-scale lubrication system to reduce the wear of tungsten carbide and cobalt and other substances, thereby significantly enhancing the bending strength, corrosion resistance and wear resistance.

[0046] Although embodiments of the present application have been shown and described, it will be understood by those having ordinary skill in the art that various changes, modifications, alternatives and variations can be made to these embodiments without departing from the principles and spirit of the present application.

[0047] The above describes the present application and its embodiments, which are not limiting, and the drawings shown are only one of the embodiments of the present application, and the actual application is not limited thereto. In summary, if a person skilled in the art is inspired, without departing from the purpose of the present application, without creative design, similar ways and embodiments of the technical solution should belong to the protection scope of the present application.

Claims

1. A highly corrosion-resistant and wear-resistant tungsten-based cemented carbide, characterized in that: The high corrosion-resistant and wear-resistant tungsten-based cemented carbide comprises the following components in parts by weight: 20-30 parts of tungsten-based composite oxide@molybdenum disulfide and boron nitride hybrid nanofibers, and 80-90 parts of graphene-coated core-shell composite powder; the tungsten-based composite oxide@molybdenum disulfide and boron nitride hybrid nanofibers are made from the following components in parts by weight: 4-6 parts of copper-nickel bimetallic MOF nanoparticles, 10-20 parts of ammonium metatungstate, 8-10 parts of polyvinylpyrrolidone, 3-5 parts of sodium molybdate dihydrate, 6-8 parts of thiourea, 0.8-1 parts of boron nitride, and 4-5 parts of Dow Corning Z-6020 silane coupling agent; the graphene-coated core-shell composite powder is a core-shell structure powder obtained by first ball milling and plasma activation treatment of tungsten carbide powder, cobalt powder, and nano-cerium dioxide powder, and then growing a graphene coating layer in situ on the surface.

2. A method for preparing a high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 1, characterized in that: Specifically, the following steps are included: S1. Tungsten carbide powder, cobalt powder, and nano-cerium dioxide powder are loaded into a ball mill jar in a mass ratio of 10:3:1-2, with a ball-to-powder ratio of 5:

1. Stearic acid is then added at 0.8-1.0% of the total powder mass. The mixture is first ball-milled at 180-200 rpm for 8-10 hours, then the speed is adjusted to 280-310 rpm for intermittent ball milling for 1-2 hours. During intermittent ball milling, the mixture is milled for 30 minutes, paused for 10 minutes, and then dry-mixed at 300 rpm for 3-4 hours. The mixture is then mixed with high-purity argon. Using a protective atmosphere, the resulting mixed powder is subjected to hydrogen plasma treatment at a power of 80-120W for 10-30 minutes. Finally, the plasma-treated mixed powder is placed in a ceramic boat, pushed into a tube furnace, sealed, evacuated, and purged with nitrogen. This process is repeated three times to complete the gas replacement. The temperature is then raised to 750-800℃ at a rate of 5℃ / min. A mixed carbon source of methanol and ethanol is introduced, and the temperature is maintained for 30-35 minutes. The temperature is then lowered to room temperature, and the product is removed to obtain graphene-coated core-shell composite powder. S2. The tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofibers and the graphene-coated core-shell composite powder described in step S1 are mixed evenly by wet ball milling. During the ball milling process, the material-to-ball ratio is 5:1, the rotation speed is 200-250 rpm, the time is 3-4 hours, and the mixture is vacuum dried at 60℃. The mixture is then placed in a mold and pressed into a green body under 300 MPa. The green body is placed in a pyrophyllite mold and sintered at high temperature and high pressure using a six-sided press, with argon gas introduced for protection. The temperature is first raised to 800℃ for 1-2 minutes, then raised to 1100-1200℃, the sintering pressure is fixed at 3-5 GPa, and the holding time is 4-8 minutes. The sample is then removed, polished, and a high corrosion-resistant and wear-resistant tungsten-based cemented carbide is obtained.

3. The method for preparing the high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 2, characterized in that: In step S1, the volume ratio of methanol to ethanol in the methanol and ethanol mixed carbon source is 3-4:

1.

4. The method for preparing the high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 3, characterized in that: The preparation method of the tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofibers specifically includes the following steps: (1) Dissolve 1.0-1.2g of copper nitrate trihydrate and 0.4-0.6g of nickel nitrate hexahydrate in 15mL of deionized water and stir for 0.5-1h to form solution I for later use. Then dissolve 0.8-1.0g of trimesic acid in 25mL of anhydrous ethanol and stir for 0.5-1h to form solution II for later use. Then mix solution I and solution II and add 0.2-0.4g of polyvinylpyrrolidone. Stir evenly and place in a reaction vessel at 110-120℃ for hydrothermal reaction for 10-12h. Wash the product with anhydrous ethanol 3-5 times and vacuum dry at 60℃ to obtain copper-nickel bimetallic MOF nanoparticles. (2) Disperse the copper-nickel bimetallic MOF nanoparticles described in step (1) in 6 mL of N,N-dimethylformamide solvent, sonicate for 30-50 min, then add ammonium metatungstate and polyvinylpyrrolidone, stir for 20-30 min to obtain the precursor spinning solution, use electrospinning technology, set the voltage to 10-18 kV and the feed rate to 0.03-0.05 mm / s, put the collected fibers into a crucible, dry them at 50-60℃ for 1-2 h, and then calcine them in air at 500-550℃ with a heating rate of 1℃ / min for 1-2 h to obtain tungsten-based composite oxide nanofibers; (3) Dissolve sodium molybdate dihydrate and thiourea in 30 mL of deionized water, then add the tungsten-based composite oxide nanofibers described in step (2), ultrasonically disperse for 10-20 min, adjust the pH to 4.0, and then react at 180-200 °C for 10-12 h. Wash the product with 80% ethanol solution 3-5 times, vacuum dry at 60 °C, and then anneal at 350-400 °C for 1-2 h in an atmosphere of 2% hydrogen and 98% argon to obtain tungsten-based composite oxide@molybdenum disulfide nanofibers. (4) Disperse 0.08-0.1g of boron nitride in 20mL of 90% ethanol solution, add 0.4-0.5mL of Dow Corning Z-6020 silane coupling agent, sonicate for 40-50min to obtain boron nitride suspension for later use, then immerse the tungsten-based composite oxide@molybdenum disulfide nanofibers obtained in step (3) into the boron nitride suspension, stir at 50-60℃ for 1-2h, vacuum dry at 80℃, and finally anneal at 300-320℃ for 0.5-1h to obtain tungsten-based composite oxide@molybdenum disulfide boron nitride hybrid nanofibers.

5. The method for preparing the high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 4, characterized in that: In step (2), the amount of ammonium metatungstate added is 1.0-2.0g, and the amount of polyvinylpyrrolidone added is 0.8-1.0g.

6. The method for preparing the high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 5, characterized in that: In step (3), the amounts of sodium molybdate dihydrate and thiourea added are 0.3-0.5g and 0.6-0.8g, respectively.

7. The method for preparing the high corrosion-resistant and wear-resistant tungsten-based cemented carbide according to claim 6, characterized in that: In step (4), the brand name of Dow Corning Z-6020 silane coupling agent is OFS-6020.

Citation Information

Patent Citations

  • Sulfide coated particle as well as preparation method and application thereof

    CN107983272A

  • Preparation method of nanometer material with carbon-coated metal particle anchoring structure

    CN110814362A

  • Water-stable copper paddle wheel metal organic framework (MOF) compositions and methods of using MOFs

    CN114206993A

  • Superfine hard alloy cutter and preparation method thereof

    CN120133526A

  • Nickel-coated copper powder, method for producing same, and conductive paste

    JP2018145448A

Cited By

  • High-purity spherical tungsten-based composite powder for plasma spraying

    CN121649382A